Developing End-of-Training Entrustable Professional Activities for Psychiatry: Results and Methodological Lessons. (July 2018) - Young, John Q.; Hasser, Caitlin; Hung, Erick K.; Kusz, Martin; O'Sullivan, Patricia S.; Stewart, Colin; Weiss, Andrea; Williams, Nancy
Abstract : Purpose: To develop entrustable professional activities (EPAs) for psychiatry and to demonstrate an innovative, validity-enhancing methodology that may be relevant to other specialties. Method: A national task force employed a three-stage process from May 2014 to February 2017 to develop EPAs for psychiatry. In stage 1, the task force used an iterative consensus-driven process to construct proposed EPAs. Each included a title, full description, and relevant competencies. In stage 2, the task force interviewed four nonpsychiatric experts in EPAs and further revised the EPAs. In stage 3, the task force performed a Delphi study of national experts in psychiatric education and assessment. All survey participants completed a brief training program on EPAs. Quantitative and qualitative analysis led to further modifications. Essentialness was measured on a five-point scale. EPAs were included if the content validity index was at least 0.8 and the lower end of the asymmetric confidence interval was not lower than 4.0. Results: Stages 1 and 2 yielded 24 and 14 EPAs, respectively. In stage 3, 31 of the 39 invited experts participated in both rounds of the Delphi study. Round 1 reduced the proposed EPAs to 13. Ten EPAs met the inclusion criteria in Round 2. Conclusions: The final EPAs provide a strong foundation for competency-based assessment in psychiatry. Methodological features such as critique by nonpsychiatry experts, a national Delphi study with frame-of-reference training, and stringent inclusion criteria strengthen the content validity of the findings and may serve as a model for future efforts in other specialties. Abstract : Supplemental Digital Content is available in the text.